Determinants of unemployment in the United States / Nurashikin Rosli - Rosli, Nurashikin (Faculty of Business Management, University Teknology MARA, 2018)
This study investigates the determinants of unemployment in the United States using annual time series data from 1980 to 2017. The analysis is carried out by reviewing the relevant literature, microeconomic and macroeconomic models of unemployment done in the past studies. As December 2017, the current unemployment rate in the United States recorded to be at 4.1 0/0. The main objective of this research is to study the recent unemployment trend in the United States. The multiple linear regression method is used in this study where the dependent variable is unemployment rate and the independent variables used in this study are consumer price index, gross domestic product, gross fixed capital formation, real wages and productivity. The data are collected from World Data Atlas, IMF Data and OECD Data. It is expected that the relationship between consumer price index and unemployment rate can be either positive or negative while the gross domestic product is having a significant and positive relationship with unemployment rate. It is expected that when gross fixed capital formation increases, unemployment rate will decrease. Real wages and unemployment rate is having a positive relationship with each other. Lastly, it is expected that the relationship between productivity and unemployment rate is not statistically significant where the relationship can be either positive or negative.